The changing role of the hospital in European health systems - McKee, Martin; Merkur, Sherry; Edwards, Nigel, 1961-; Nolte, Ellen (Cambridge : Cambridge University Press, 2020)
Hospitals today face a huge number of challenges, including new patterns of disease, rapidly evolving medical technologies, ageing populations and continuing budget constraints. This book is written by clinicians for clinicians and hospital managers, and those who design and operate hospitals. It sets out why hospitals need to change as the patients they treat and the technology to treat them changes. In a series of chapters by leading authorities in their field, it challenges existing models, reviews best practice from many countries and presents clear policy recommendations for policymakers and hospital administrators. It covers the main patient groups and conditions as well as those departments that make modern effective care possible, in imaging and laboratory medicine. Each chapter looks at patient pathways, aspects of workforce, required levels of specialisation and technology, and the opportunities and challenges for optimising the delivery of services in the hospital of the future. This title is also available as Open Access on Cambridge Core.
Introduction - The changing nature of care provided in the hospital -- The challenges of adapting hospital care for children -- Patients with stroke -- Meeting the needs of frail older patients -- Oncological hospital care -- COPD as an exemplar of a chronic health condition -- Emergency medicine -- Advances in perioperative medicine -- Advances in imaging -- Advances in laboratory medicine -- Conclusions - Challenges for hospitals of the future.
Title from publisher's bibliographic system (viewed on 07 Jul 2020).
Keywords: Health services administration -- Europe